Performance evaluation of tuberculosis control in Brazilian municipalities - Pinto, Priscila Fernanda Porto Scaff; Santos, Beatriz Pinheiro Schindler dos; Teixeira, Camila Silveira Silva; Nery, Joilda Silva; Amorim, Leila Denise Alves Ferreira; Sanchez, Mauro Niskier; Barreto, Mauricio Lima; Pescarini, Julia Moreira (Revista de Saúde Pública, 2022)
OBJECTIVE To evaluate the performance of tuberculosis control in Brazilian municipalities. METHODS This is an ecological study on Brazilian municipalities that notified at least four new cases of tuberculosis, with a minimum of one new case of pulmonary tuberculosis between 2015 and 2018. The municipalities were stratified according to the population in < 50 thousand, 50–100 thousand, 100–300 thousand, and > 300 thousand inhabitants, and the k-means method was used to group them within each population range according to the performance of six indicators of the disease. RESULTS A total of 2,845 Brazilian municipalities were included, comprising 98.5% (208,007/211,174) of new tuberculosis cases in the period. For each population range, three groups (A, B, and C) of municipalities were identified according to the performance of the indicators: A, the most satisfactory; B, the intermediates; and C, the least satisfactory. Municipalities in group A with < 100 thousand inhabitants presented results above the targets for laboratory confirmation (≥ 72%), abandonment (≤ 5%), and cure (≥ 90%), and comprised 2% of new cases of the disease. Conversely, municipalities of groups B and C presented at least five indicators with results below the targets – HIV testing (< 100%), contact investigation (< 90%), directly observed therapy (< 90%), abandonment (> 5%), and cure (< 90%) –, and corresponded to 66.7% of new cases of tuberculosis. In group C of municipalities with > 300 thousand inhabitants, which included 19 of the 27 capitals and 43.1% of new cases of tuberculosis, the lowest percentages of contact investigation (mean = 56.4%) and directly observed therapy (mean = 15.4%) were verified, in addition to high abandonment (mean = 13.9%) and low coverage of primary health care (mean = 66.0%). CONCLUSIONS Most new cases of tuberculosis occurred in municipalities with unsatisfactory performance for disease control. Expanding the coverage of primary health care in these places can reduce abandonment and increase the contact investigation and directly observed therapy.